Effectiveness of Oral Versus Vaginal Administration of Misoprostol for the Termination of Pregnancy: A Cross-Sectional Study - Zubeda Bhutto, Farkhunda Khursheed, Maliha Fatima, Ifat Balouch, Humaira Tahir, Asma Haque (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the acceptability and effectiveness of oral versus vaginal administration of misoprostol to terminate the pregnancy in the first trimester. Study design: A cross-sectional study Place and Duration: This study was conducted at Dow University Hospital, Dow University of Health Sciences Karachi, Pakistan from August 2020 to August 2021 Methodology: The study included 120 women, out of which 52 women had taken misoprostol orally and in 68 women, the drug was introduced via vaginal route, 4 hours before the surgery, and data was collected including abdominal pain and vaginal bleeding by a questionnaire. Results: No significant differences were observed in terms of cervical dilatation, however, bleeding was more in the vaginal group i.e. 42% when compared with the oral group in which 24% of women experienced bleeding. Similarly, 89% of women of the oral group were satisfied with the results whereas 75% of patients of the vaginal group were satisfied with the results. Conclusion: Although the effectiveness of misoprostol is similar in both groups, more women of the oral group were satisfied and thus it could be chosen as an effective alternative to vaginal administration of misoprostol.